The k-Derivation Acting as a k-Endomorphism and as an Anti-k-Endomorphism on Semiprime Nobusawa Gamma Ring - Chakraborty, Sujoy; Paul, Akhil Chandra (GANIT: Journal of Bangladesh Mathematical Society, 2014)
This article defines k-endomorphism and anti-k-endomorphism on ?N-rings, and uses the concept of k-derivation of ?N-rings. Considering M as a semiprime ?N-ring and d as a k-derivation of M, it aims to prove that (i) if d acts as a k-endomorphism on M such that M?M=M and xk(?)x=0 for all x?M and ?? ?, then d=0; and (ii) if d is acting as an anti-k-endomorphism on M such that M?M=M, xk(?)x=0 and k(?)x?=?xk(?) for all x?M and ?? ?, then d=0. GANIT J. Bangladesh Math. Soc. Vol. 33 (2013) 93-101 DOI: http://dx.doi.org/10.3329/ganit.v33i0.17663